Effects of sludge pellet mulch on soil physicochemical properties and soil enzyme activities - Mo, Qian; Sun, Haiyan; Wang, Yuying; Song, Shuying; Zhang, Xue; He, Ting; Zhuo, Chengrui (Journal of Environmental Engineering and Landscape Management, 2024)
The drinking-water treatment sludge (DWTS) possesses intricate characteristics, which restrict its broad applicability. To tackle this issue, we employed DWTS obtained from the Minhang District of Shanghai as the primary constituent, blending it with a low-alkaline curing material to produce pelletized mulch. This investigation primarily focuses on evaluating the environmental safety of sludge pellet mulch (SPM) and scrutinizing alterations in soil physicochemical properties at various mulch thicknesses. The outcomes affirm the durability of SPM and the compliance of eight heavy metals with prescribed standards concerning their concentration, pH, and EC values. After applying SPM, noteworthy enhancements were observed in soil moisture, organic matter content, available nutrients, and the activity of four enzymes. Furthermore, a reduction in soil temperature was observed. For urban landscape mulching, SPM within the range of 9.6–28.8 kg/m2 emerged as the preferred choice, yielding the most favorable overall soil quality improvements.